Дијагностичка вредност серума Ahd-5, IL1RL1 и CD138 код пацијената са хроничном срчаном инсуфицијенцијом: Серум Ахд-5, ИЛ1РЛ1 и ЦД138 код КХД-а - Ruan, Wenqiang; Wang, Jiajia; Li, Lingyun; Jia, Yuanchao (Journal of Medical Biochemistry, 2026)
Objective To explore the diagnostic value of serum Aldehyde dehydrogenase 5 (Ahd-5), IL-1 receptor-like 1 (IL1RL1), and CD138 in patients with chronic heart failure (CHF). Methods The study group consisted of 256 CHF patients who were treated at our hospital between February 2023 and March 2025, whereas the control group consisted of 138 healthy volunteers who came to our hospital during that period for physical examinations. The cardiovascular function markers (LVEF, LVESV and LVEEDV) as well as the serum markers (Ahd-5, IL1RL1, CD138, and N-terminal pro-B-type natriuretic peptide, or NT-proBNP), were identified and compared. According to the LVEF results, the CHF patients were divided into the reduced ejection fraction heart failure (HFrEF) group, the mildly reduced ejection fraction heart failure (HFmrEF) group, and the preserved ejection fraction heart failure (HFpEF) group. Serum Ahd-5, IL1RL1, and CD138 levels of CHF patients were correlated with cardiac function markers using Pearson correlation analysis. The associations among the various severities of CHF patients and their serum Ahd-5, IL1RL1, and CD138 levels were examined using Spearman correlation analysis. The factors impacting the occurrence of CHF were examined. The diagnostic value of serum Ahd-5, IL1RL1, and CD138 levels for CHF patients was examined using a receiver operating characteristic (ROC) curve. Results Compared to the control group, the study group’s serum levels of Ahd-5 and LVEF were significantly lower (P<0.05), although their blood levels of IL1RL1, CD138, NT-proBNP, creatinine, LVESV, and LVEDV were significantly greater. According to the LVEF data for CHF patients, there were 72 patients in the HFrEF group, 88 in the HFmrEF group, and 98 in the HFpEF group. Serum Ahd-5 levels were substantially lower in the HFrEF and HFmrEF groups than in the HFpEF group (P<0.05), although serum IL1RL1 and CD138 levels were significantly greater. While the HFmrEF group had considerably greater serum IL1RL1 and CD138 levels (P<0.05), the HFrEF group had significantly lower serum Ahd-5 levels. According to the results of the Pearson correlation analysis, the serum Ahd-5 level of CHF patients was positively correlated with LVEF (P<0.05) and negatively correlated with NT-proBNP, creatinine levels, LVESV, and LVEDV (P<0.05); the serum levels of IL1RL1 and CD138 were positively correlated with NT-proBNP, creatinine levels, LVESV, and LVEDV (P<0.05) and negatively correlated with LVEF (P<0.05). The serum Ahd-5 level showed a negative correlation with IL1RL1 and CD138 levels (P<0.05), and the serum IL1RL1 level had a positive correlation with the serum CD138 level (P<0.05). The areas under the curve (AUCs) of serum Ahd-5, IL1RL1, and CD138 for diagnosing CHF alone were 0.851, 0.830, and 0.860, according to ROC curve analysis. The combined diagnosis of CHF had an AUC of 0.946, which was substantially higher than the AUCs of serum Ahd-5 (Z = 2.755, P = 0.009), IL1RL1 (Z = 3.071, P = 0.002), and CD138 (Z = 2.321, P = 0.023). Conclusion While serum IL1RL1 and CD138 levels considerably increased in CHF patients, serum Ahd-5 levels significantly decreased. When these three indications are detected together, they have a high diagnostic value for CHF and could be used as a novel auxiliary approach.